Comparative Study of Catalytic Systems T iO2 and N b2O5 (2012)
This article discusses the viability of using agents such as niobium photocatalyst in decreasing higher energy of the band gap. To do so competitively withT iO2, the presence of oxidation helpers such as H2O2 and O3 could present surprising results in the catalytic performance due to higher generation of OH o radicals. Oxidation helpers are shown to assist in obtaining larger are oxides and textural properties diﬀerent from commercial niobium oxide, and enhancing its catalytic activity in free cyanide removing. The article presents experimental results of cyanide photodegradation of 100mg/l with Degussa P-25 T iO2 and Nb2O53H2O, using a type CPC photoreactor and sunlight as the radiation source. Taking an inclination equal to Cartagena latitude of 10,450, the results show a clear eﬀect of pH, catalyst type and oxidation auxiliar agenton photodegradation reaction. The ion cyanide reduction of polluted eﬄuent was enhanced by oxidizing agent (O3 and H2O2) addition. This may suggest a greater susceptibility to free cyanide oxidation and cianate indirect oxidation due to higher hydroxyl radical generation, which was induced by H2O2or O3 presence under solar radiation. The results showed free cyanide photocatalytic oxidation percentages between 64% and 72% using Nb2O5 3H2Oand 67% and 71% using T iO2 Degussa P-25. The catalysts were characterized structurally by XRD, BET, Raman and FTIR, with the purpose of correlating morphological changes in catalytic performing.